Efficient and selective oxidation of sulfides in batch and continuous flow using styrene-based polymer immobilised ionic liquid phase supported peroxotungstates12. Issue 77 (2nd August 2016) - Doherty, S.; Knight, J. G.; Carroll, M. A.; Clemmet, A. R.; Ellison, J. R.; Backhouse, T.; Holmes, N.; Thompson, L. A.; Bourne, R. A.
Abstract : Good conversion and high selectivity for sulfoxidation have been achieved under segmented and continuous flow using a polystyrene-based polymer immobilised ionic liquid phase (PIILP) peroxotungstate. Abstract : Styrene-based peroxotungstate-modified polymer immobilized ionic liquid phase catalysts [PO4 {WO(O2 )2 }4 ]@ImPIILP (Im = imidazolium) are remarkably efficient systems for the selective oxidation of sulfides under mild conditions both in batch and as a segmented or continuous flow process using ethanol as the solvent and mobile phase, respectively. The performance of these styrene-based systems has been compared against their ring opening metathesis polymerisation derived counterparts to assess their relative merits. A comparative survey revealed the catalyst supported on N -benzyl imidazolium decorated polymer immobilised ionic liquid to be the most efficient and a cartridge packed with a mixture of [PO4 {WO(O2 )2 }4 ]@ImPIILP and silica operated as a segmented or continuous flow system giving good conversions and high selectivity for sulfoxide. The immobilised catalyst remained highly active for the sulfoxidation of thioanisole in ethanol with a stable conversion–selectivity profile for up to 8 h under continuous flow operation; for comparison conversions with a mixture of [NBu4 ]3 [PO4 {WO(O2 )2 }4 ] and silica dropped dramatically after only 15 min as a result of rapid leaching while [PO4 {WO(O2 )2 }4 ]@ImPIILP prepared from commercially available Merrifield resin also gave consistently lower conversions; these benchmark comparisons serve to underpin the potential benefits of preparing the polymer immobilized ionic liquid supports.